Thermal treatment of plutonium contaminated material (PCM) waste. (13th February 2017) - Boast, Luke; Stennett, M.C.; Hyatt, Neil C.
ABSTRACT: Key drivers for the application of thermal treatment processes include the reduced volume, improved passive safety, and superior long term stability of the vitrified wasteform products. These advantages have led to a renewed interest in thermally treating various UK ILW streams. To support the increased investment in thermal treatment technologies a fundamental understanding of the processes and the impact of waste inventory needs to be established. The research described in this report aims to provide the evidence necessary to support a major investment in thermal treatment of Plutonium Contaminated Materials (PCM). The report describes the use of laboratory scale waste simulants to develop an understanding of the waste and matrix interactions during thermal treatment of PCM waste. The report includes the thermal treatment process and characterization of the vitrified product.